Fair Competition in The Digital Era: Indonesia’s Tax Reform Through Significant Economic Presence - Devina Puspita Sari; Sy. Muhammad Ikhsan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study examines the development of the Permanent Establishment concept within the Indonesian tax system, the transition to the Significant Economic Presence (SEP) concept under Tax Harmonization Law. The emergence of SEP was driven by digital cross-border business models that allow multinational enterprises to derive economic benefits from Indonesia without a physical presence or permanent establishment. This study is a normative juridical, applying legislative and conceptual approaches in analyzing regulations concerning place of business and SEP concept, as well as to assess their implications for competition law in Indonesia. The research findings indicate that the implementation of SEP constitutes a strategic government measure to broaden the taxation base and overcome the limitations of the place-of-business concept, which previously focused on physical presence. By establishing criteria based on transaction value, number of users, and consolidated gross turnover, SEP provides a legal basis for taxing foreign companies that derive economic benefits from Indonesia, while also promoting fair business competition by closing loopholes for tax avoidance, align with the aims of the Anti-Monopoly Law, which ensuring equal business opportunities, safeguarding the public interest, and fostering a fair, conducive, and efficient business climate.